How is different muscle fibre typology a factor to explain variable responses to training? - Lievens, E.; Bellinge, P. (2020)
Those familiar with the HIIT Science material, know the issue all too well. There is the training load an athlete encounters, which we have some level of control over. But then there is the training load response — a completely different beast. This issue, and the problem it can cause, has frustrated athletes, teams and coaches for years.